A. \(2 \pm 2\sqrt 2 i\).
B. \( - 2 \pm 2\sqrt 2 i\).
C. \( - 1 \pm 2\sqrt 2 i\).
D. \(1 \pm \sqrt 2 i\).
D
\(\begin{array}{l}{z^2} - 2z + 3 = 0\\ \Leftrightarrow \left( {{z^2} - 2z + 1} \right) + 2 = 0\\ \Leftrightarrow {\left( {z - 1} \right)^2} + 2 = 0\\ \Leftrightarrow {\left( {z - 1} \right)^2} = - 2\\ \Rightarrow \left[ \begin{array}{l}z - 1 = i\sqrt 2 \\z - 1 = - i\sqrt 2 \end{array} \right. \Leftrightarrow \left[ \begin{array}{l}z = 1 + i\sqrt 2 \\z = 1 - i\sqrt 2 \end{array} \right.\end{array}\)
Câu hỏi trên thuộc đề trắc nghiệm dưới đây !
Copyright © 2021 HOCTAP247